PEMBUATAN SISTEM INFORMASI BERBASIS WEB PADA SDN CIWEDUS KEC. KASEMEN KOTA SERANG - Waliadi Gunawan; Edi Rakhmat; Teguh Rohman Nidayan (LPPM Unbaja, 2019)
Along with the development of the world of technology and information. Website is an information mediathat offers various facilities in presenting information. Speed and comfort are positive values for theinternet, especially for computer devices. The technology has changed the way of life of society andinfluences some aspects of life. Computers are now one of the devices whose existence is very useful for thecommunity. Various computer uses in life include use in the fields of communication, education, health,planning, and various other uses. Computers can help humans in completing various kinds of work quickly,precisely, and accurately so as to reduce errors that might arise if done with work done manually. Basedon this background the author plans to create a web-based school information system so that he can helpfind information and can provide an introduction to Ciwedus SDN in the internet world. The use of thisschool's web information system is an appropriate step to facilitate the information process of thecommunity at Ciwedus Elementary School in the past and at any time, the recording of Teacher and studentdata, and student data searches, and the reports produced are better and more accurate.